Enhancing Knowledge Management Development in Cargo Companies through Agile Principles and Practices - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research highlights the significant problems the cargo industry faces in managing knowledge to improve operational efficiency, overcome competition, and meet increasingly complex customer needs. Applying an Agile approach to knowledge management (KM) development in a cargo company, this research designed and implemented a responsive, adaptive, and high-quality KM solution through a series of stages such as requirements definition, planning, development, and testing. The results showed significant improvements in operational efficiency, more vital cross-team collaboration, and more accurate data-driven decision-making. At the same time, a thorough testing process proved the optimal usability, performance, and security of the developed KM solution. This research contributes to developing KM theory and practice in the cargo industry. It highlights the value of applying Agile principles in improving operational efficiency and providing significant added value to cargo companies in managing their knowledge in today's digital age.